Iowa Birdline update, November 5-7, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Email of the Iowa Birdline update for November 5-7, 1990. Highlights of the update include sightings of a Pacific Loon, a Red-throated Loon, and a Varied Thrush. Also of note was the continued presence of a first winter California Gull and a first winter Lesser Black-backed Gull. Also included are handwritten notes for the next week's update, including sightings of a Black-legged Kittiwake and a Surf Scoter. Epson - sheet feed/flatbed